2022
DOI: 10.17219/acem/149728
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping in heart failure with preserved ejection fraction: A key to find effective treatment

Abstract: Heart failure with preserved ejection fraction (HFpEF) is an increasingly widespread medical condition, with excessive morbidity and mortality. Recently, for the first time in HFpEF, a reduction in the primary composite outcome of cardiovascular death or HF hospitalization was shown with empagliflozin. The failure of previous clinical trials in HFpEF might have resulted from suboptimal patient selection and inclusion of patients without "true" or clinically significant HFpEF. Another important factor might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Previous studies have demonstrated that HFpEF includes multiple etiologies of heart failure. Phenotyping of the disease according to etiology can provide further insights into the pathophysiology and management of HFpEF [16] . Furthermore, our study consisted of patients with normal weight/overweight rather than obese patients who are well known to have HFpEF [33] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that HFpEF includes multiple etiologies of heart failure. Phenotyping of the disease according to etiology can provide further insights into the pathophysiology and management of HFpEF [16] . Furthermore, our study consisted of patients with normal weight/overweight rather than obese patients who are well known to have HFpEF [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CMD, especially HFpEF, was not assessed as a potent cause of subclinical HF in the present study. CMD can account for up to two-thirds of symptomatic ischemic heart disease patients without epicardial coronary artery stenosis [16] . Löffler et al demonstrated that HFpEF patients had a higher prevalence of CMD and diffuse fibrosis with decreased exercise tolerance than healthy controls, although LVGLS tended to be higher in the latter [34] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA relies on a probabilistic model to describe the distribution of data, which is used to derive clusters from the data based on the probabilities that certain cases belong to certain latent classes, and relies less on a distance measure to find the clusters. Overall, these techniques offer promising tools and research approaches to identify sub-phenotypes of diseases such as HFpEF and can help to improve diagnosis, treatment, and prognosis from multiple dimensions, including clinical data, biomarkers, or imaging studies [ 7 , 13 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Herein, we listed several key landmark studies unraveling AI-based learning and phenotyping among the HFpEF population.…”
Section: Clinical Entitiesmentioning
confidence: 99%
“…Additionally, imaging can exclude alternative diagnoses that mimic HFpEF, such as hypertrophic cardiomyopathy, primary valvular heart disease, cardiac amyloidosis, and pericardial disease. While two-dimensional (2-D) transthoracic echocardiography is the most commonly used imaging modality, advanced imaging techniques, including cardiac magnetic resonance imaging and 2-D speckle tracking echocardiography, are used to identify distinct HFpEF phenotypes based on left ventricular structure and function [ 13 , 23 , 28 , 29 , 30 , 31 , 32 , 35 ]. Compared with standard 2-D echocardiography, three-dimensional (3-D) echocardiography provides a more reliable and reproducible evaluation of cardiac chamber volumes, mass, and shape, which are highly correlated with cardiac magnetic resonance imaging (CMR) [ 36 ].…”
Section: Imagingmentioning
confidence: 99%